2021
DOI: 10.1002/pat.5576
|View full text |Cite
|
Sign up to set email alerts
|

A writable aniline‐functionalized polydiacetylene composite with obvious colorimetric change upon both heating and near infrared lights irradiation

Abstract: Due to the unique optical and chromatic properties toward various external stimuli, conjugated polydiacetylene (PDA) materials are attracting a great attention from scientists. And the fabrication of PDA embedded composites would further expand the application prospect. In this work, aniline substituted diacetylene derivative was embedded into wax matrix to form a writable composite. After UV induced 1,4-topochemical polymerization, the patterns generated from the PDA/wax composite showed clearly a blue-to-pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…As a reference, both our group and others have reported that the aniline substituted PCDA (PCDA-AN) showed a poor thermal stability and completely irreversible thermochromism after photopolymerization (Scheme S2, Supporting Information). [24,25] Besides, because of the absence of hydrophilic head group, PCDA-AN could not form vesicle in aqueous solution. [26] And in this work the introduction of benzaldehyde group is anticipated to bring in a stronger intermolecular interaction among polymer side chains and lead to a more stable thermal responsive behavior for PDA.…”
Section: Thermal Stability and Thermochromism Of The Poly(pcda-ba) Ve...mentioning
confidence: 99%
“…As a reference, both our group and others have reported that the aniline substituted PCDA (PCDA-AN) showed a poor thermal stability and completely irreversible thermochromism after photopolymerization (Scheme S2, Supporting Information). [24,25] Besides, because of the absence of hydrophilic head group, PCDA-AN could not form vesicle in aqueous solution. [26] And in this work the introduction of benzaldehyde group is anticipated to bring in a stronger intermolecular interaction among polymer side chains and lead to a more stable thermal responsive behavior for PDA.…”
Section: Thermal Stability and Thermochromism Of The Poly(pcda-ba) Ve...mentioning
confidence: 99%